Transcranial Direct Current Stimulation for Post-Concussion Syndrome: Study Protocol for a Randomized Crossover Trial - de Amorim, Robson Luis Oliveira; Brunoni, André Russowsky; de Oliveira, Mirian Akiko Furutani; Zaninotto, Ana Luiza Costa; Nagumo, Marcia Mitie; Guirado, Vinícius Monteiro de Paula; Neville, Iuri Santana; Benute, Gláucia Rosana Guerra; de Lucia, Mara Cristina Souza; Paiva, Wellingson Silva; de Andrade, Almir Ferreira; Teixeira, Manoel Jacobsen (Frontiers in Neurology, 2017)
Background: Mild traumatic brain injury (MTBI) represents 70-80% of all treated brain injuries. A considerable proportion of MTBI patients experience post-concussion symptoms for a prolonged period after MTBI, and these symptoms are diagnosed as persistent post-concussion syndrome (PPCS). PPCS is defined as a range of physical, cognitive and emotional symptoms. However, memory and executive dysfunction seems to be one of the most debilitating symptoms. Recently, non-invasive brain stimulation has been studied as a potential treatment method for traumatic brain injury (TBI) patients. Therefore, our primary goal is to verify the effects of TDCS in patients with PPCS who demonstrate cognitive deficits in long-term episodic memory, working memory and executive function following MTBI. Methods/design: This is a randomized crossover trial of patients with a history of MTBI with cognitive deficits in memory and executive function. Thirty adult patients will be randomized in a crossover manner to receive three weekly sessions of anodal tDCS (2mA) at left dorsolateral prefrontal cortex, left temporal cortex and sham stimulation that will be performed at 7-day intervals (washout period). The clinical diagnosis of PPCS will be determined using the Rivermead Post Concussion Symptoms Questionnaire. Patients who meet the inclusion criteria will be assessed with a neuropsychological evaluation. A new battery of computerized neuropsychological tests will be performed before and immediately after each stimulation. Statistical analysis will be performed to determine trends of cognitive improvement. Discussion: There are paucity of studies regarding the use of TDCS in TBI patients and, although recent results showed controversial data regarding the effects of TDCS in such patients, we will address specifically patients with PPCS and MTBI, and no brain abnormalities on CT scan other than subarachnoid hemorrhage. Moreover, due to the missing information on literature regarding the best brain region to be studied we will evaluate two different regions to find immediate effects of TDCS on memory and executive dysfunction. Ethics and dissemination: Ethics approval has been obtained from the Ethics Committee for review of research projects, Hospital das Clínicas, University of São Paulo (CAPPesq 612.643/14).